The role of motivation and supervision on the performance of post office employees in the Central Kalimantan regional office - Rita Yuanita Toendan; Hansly Tunjang (Jurnal Mantik, 2023)
Research in the field of HR Management is the basis for research to improve employee performance. Various methods are carried out with motivation and work supervision as variables that are expected to improve performance at PT. POS Indonesia in Palangka Raya City. Quantitative research on 35 employees and the analytical tools used by SPSS. 22.0. The results prove the importance of the role of motivation and supervision by 62%. The research implications provide benefits for improving performance which currently tends to be weak in performance by providing motivation and intensive supervision of work in accordance with the vision and mission. This research can support performance improvement in the field of HR and further research can mediate competencies